Management of the Arabic language teacher recruitment program in the city of Pekanbaru - Rahmah Arisa; Hakmi Wahyudi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes the management of the Arabic language teacher recruitment program in Pekanbaru City, Riau, focusing on the stages of recruitment, selection, placement, needs planning, and teacher competency standards. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving eight participants from two representative schools. The findings indicate that the recruitment process has generally been well-structured through stages of needs analysis, administrative screening, interviews, and competency testing, although objectivity and transparency remain key challenges. Teacher requirement planning is based on student-teacher ratios and curriculum demands but is often constrained by changes in field conditions. Competency and qualification standards largely follow Permendiknas No. 16 of 2007, yet digital literacy and pedagogical innovation require improvement. Overall, this study contributes a contextual framework for managing Arabic teacher recruitment that integrates professionalism, transparency, and Islamic educational values to enhance the quality and sustainability of Arabic language education.